Dr. Warren French
Doctor Warren French lecturing at Nantucket Conference. Virginia Scardiglia and Elaine Steinbeck in foreground. Photo located in 'Special Events Photo Archive' binder in the Martha Heasley Cox Center for Steinbeck Studies. Virginia Scardiglia was one of the friends of John Steinbeck and Ed Ricketts who met on a regular basis at Ricketts' laboratory on Cannery Row, Monterey, Ca.